American Dad! Volume 6 - MacFarlane, Seth, 1973-; Barker, Mike, 1968-; Weitzman, Matt; Schaal, Wendy, 1954-; Grimes, Scott, 1971-; MacFarlane, Rachael, 1976-; Baker, Dee Bradley; Twentieth Century-Fox Television, Inc.; Twentieth Century Fox Home Entertainment, Inc.; Copyright Collection (Library of Congress) (Beverly Hills, California : Twentieth Century Fox Home Entertainment, 2011)
Bumbling CIA operative Stan Smith will stop at nothing to defend everything that makes this country great, from strip bars to that most sacred of American institutions, The Goonies! Whether he's trading brains with a racehorse or rescuing Roger from bloodthirsty revolutionaries, Stan will do whatever it takes to secure the blessings of liberty in this over-the-top salute to the greatest nation on Earth. Extras included.
In country-- club -- Moon over Isla island -- Home adrone -- Brains, brains and automobiles -- Man in the moonbounce -- Shallow vows -- My morning straitjacket -- G-string circus -- Rapture's delight -- Don't look a Smith horse in the mouth -- A Jones for a Smith -- May the best Stan win -- Return of the bling -- Cops and Roger -- Merlot down dirty shame -- Bully for Steve -- An incident at Owl Creek -- The great space roaster.
Wide screen (1.78:1), full screen (1.33:1), dual layer.
Originally broadcast on television in 2009 and 2010.
"Uncensored and outrageous"--Container.
Release date: April 19, 2011.
Title from container.
Special features: Audio commentary on selected episodes; uncensored audio and/or video on selected episodes; deleted scenes; making of Rapture's delight; Rapture's delight broadcast script; alternate commentary on selected episodes featuring The interdisciplinary collective for America dad studies; American dad honors its four-legged friends.
Keywords: Families -- Drama; Life on other planets -- Drama; Intelligence officers -- United States -- Drama; Television comedies; Animated television programs; Fiction television programs; Video recordings for the hearing impaired